Simulações computacionais 3D no VPython : um ambiente de aprendizagem para a física dos fluidos - Assis, Bruna Camargo Soares de (2017)
In the midst of so many technological innovations, we live in a moment when we are influenced by a diversity of visual pedagogical resources available for the teaching of Physics. Inside this universe together with some knowledge related to the concepts of learning objects in the view of Meaningful Learning Ausubel, we have developed computational animations, using the 3D Visual Python graphical module (VPython), in order to study phenomena related to Fluid Physics (of liquids in particular). We present a proposal that will enable the Physics teacher to teach his contents in an attractive, dynamic and interactive way, placing the student as an active subject in the learning process. We hope that this pedagogical investment will bring benefits capable of producing meaningful learning of new concepts and also of expanding and strengthening the bond between teacher and student in the classroom. Inside the chosen area we work with concepts of force, with emphasis on the thrust and friction caused by a fluid, as well as density. We have done this by employing the animations in three ways: (a) considering bodies with different densities immersed in a container containing some kind of liquid (eg water), (B) considering bodies with equal densities and different forms, and finally (c) the flow of a fluid through a small hole in the wall of the container containing it. The animations were applied in the classroom in October 2016 to 13 students of the 1st Year of High School of a school located in the city of Iporá – Goiás, and the results obtained through a pre-test and a final test were analyzed, revealing that the animations contributed effectively to the learning of the concepts involved, and that the degree of motivation that this virtual tool provided for the learning process was very exciting.